Strategi Pengelolaan Wakaf Uang oleh Badan Wakaf Indonesia (BWI) - Neneng Hasanah; Indah Sulistya; M. Iqbal Irfany (Badan Wakaf Indonesia, 2020)
Abstract: The Indonesian Waqf Board (BWI) is a national nazhir which was established with a vision and mission to advance the system of representation in Indonesia. BWI has important responsibilities in empowering waqf assets, including cash waqf. Cash waqf is one of the products of business character representation and can be an alternative to produce other waqf assets. To achieve these objectives, the management sector becomes the main sector to generate profits on a sustainable basis. Therefore, the purpose of this study is to identify internal factors (strengths and weaknesses) and external factors (opportunities and threats) that influence them based on the business model canvas. Data processing and techniques use the Analytic Network Process (ANP) with a SWOT network structure to obtain priority strategies that can be applied. From these results, five alternative strategies were obtained with the highest priority is increasing nazhir professionalism in terms of entrepreneurial waqf management. Keywords: ANP, business canvas model, cash waqf, strategy, SWOT.